The Empirical Relevance of the New Economic Geography: Testing for a Spatial Wage Structure in Germany - Steven Brakman; Harry Garretsen; Marc Schramm (Center for Economic Studies and ifo Institute (CESifo), 2000)
In this paper we want to shed some light on the empirical relevance of the new economic geography. Using one of the central features of the core new economic geography models, namely that wages have the tendency to fall the further one moves away from centres of economic activity, we investigate the existence of a spatial wage structure for post-unification Germany. We find support for a spatial wage structure for German city-district wages, and hence indirectly for the relevance of a new economic geography model for Germany. We also find that demand linkages in Germany are strongly localised and that the old border still matters to the extent that economic interactions between western and eastern Germany are still limited compared to the situation within these two parts of Germany.
Keywords: F12; F15; R12; 330; New economic geography; spatial wage structure; Germany